Gallbladder perforation: a rare complication of postoperative chemotherapy of gastric cancer - Sun, Yanlai (World J Surg Oncol, 2015)
A middle-aged man presented 1 day after being discharged from hospital with completing the first course of postoperative chemotherapy. He suffered a sudden persistent high fever and chills. It was noted that he had a history of a total gastrectomy (with D2 lymphadenectomy) 1 month ago. His admission bloods revealed total bilirubin was 142.2umol/L , indirect bilirubin of 107.6umol/L and white cell count of 20.05×10(9)/L. A color doppler ultrasound scan confirmed fluid and gas around liver and hilus lienis while the gallbladder cannot be detected. During Computed Tomography (CT) guided puncture positioning technology and setting a three-channel tube, about 400 ml of foul smell hazel turbid liquid was drained out. He was diagnosed as gallbladder perforation and he was underwent conservative treatment consist of drainage, banning diet, total parenteral nutrition and intravenous antibiotics. Then he recovered well within the subsequent 10 days and was discharged.